The Role and Legal Position of a Notary in the Process of Making a Deed of Change in Management of a Limited Liability Company (CV) Due to Death - Maulidya, Ainun (TABELLIUS: Journal of Law, 2023)
A Limited Liability Company can remain in existence, either with the participation of the heirs of the deceased members, or only between the remaining members as long as these conditions have been agreed upon in advance by including them in the articles of association of the CV. This writing aims to determine and analyze the role and legal position of the Notary in making a deed of change in management of a limited partnership company (CV) due to death, the legal position of the deed clauses made by a Notary in making a deed of change in management of a limited partnership company (CV) because of death. The approach method used in this research is a sociological juridical approach, meaning research carried out on the real conditions of society or the community environment with the aim and purpose of finding facts which then lead to identification and ultimately lead to problem solving. The analytical knife in this writing uses the theory of authority and the theory of legal certainty. The results of this research show that the procedure for changing the CV management company by a successor is that there must be provisions confirming the ability to continue the CV must be clearly stated in the CV's articles of association agreement, after which all deeds are registered and announced in the Supplement to the State Gazette. The position of the clause on changing the managing partner from the notary to the heirs is to explain and strengthen the position of the heirs as managing partners. Even though the deed of establishment of CV does not contain a clause on changing the heirs of the management company, the process of changing heirs is still ongoing. Keywords: Company; Dies; Liability; Notary.